A-Z of nutritional supplements: dietary supplements, sports nutrition foods and ergogenic aids for health and performance: Part 40 - Larson-Meyer, D. E.; Burke, L. M.; Stear, S. J.; Castell, L. M. (British Journal of Sports Medicine, 2013)
As mentioned before, micronutrients, including vitamin supplements, are widely used in the general population and by athletes, and have a variety of clinical applications. Similar to Part 39, we have again devoted an entire part of our A-Z series to vitamin supplementation—this time to vitamin D. Vitamin D was first discussed in our A-Z series in an earlier article on calcium and other bone health nutrients in 20101. In Part 40, the topic of vitamin D has been discussed anew by our current author in the context of more recent literature.